1993
DOI: 10.4098/at.arch.93-20
|View full text |Cite
|
Sign up to set email alerts
|

Diet of wolves in the Bieszczady Mountains, Poland

Abstract: The diet of wolves Canis lupus Linnaeus, 1758 was studied from October 1989 to November 1992 in the Bieszczady Mountains, southeastern Poland. A total of 221 wolf scats were collected and analyzed to determine the prey species consumed by wolves in each season. Cervids (red and roe deer) obviously predominated in wolf diet and consisted from 65% of winter biomass to 96% of summer biomass consumed. The red deer made up approximately 95% and roe deer only 5% of total cervid biomass consumed. During summer deer f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 10 publications
6
38
1
2
Order By: Relevance
“…In all locations in Europe, wolves killed mainly young wild boar (Gavrin and Donaurov 1954, Lavov 1972, Ryabov 1974, Gatikh 1979, Rusakov 1979b, Kuzmin and Khakhin 1980, Litvinov 1981, Kudaktin 1982, Brtek and Voskâr 1987, Kochetkov 1988, Jędrzejewski et al 1992, Śmietana and Klimek 1993, Kuchmel 1994, Mattioli et al 1995. A similar pattern of wolf predation on wild boar was reported in Asia (Abdunazarov and Taryannikov 1991).…”
Section: Effects Of Wolf Predation On Ungulate Communitiessupporting
confidence: 56%
See 3 more Smart Citations
“…In all locations in Europe, wolves killed mainly young wild boar (Gavrin and Donaurov 1954, Lavov 1972, Ryabov 1974, Gatikh 1979, Rusakov 1979b, Kuzmin and Khakhin 1980, Litvinov 1981, Kudaktin 1982, Brtek and Voskâr 1987, Kochetkov 1988, Jędrzejewski et al 1992, Śmietana and Klimek 1993, Kuchmel 1994, Mattioli et al 1995. A similar pattern of wolf predation on wild boar was reported in Asia (Abdunazarov and Taryannikov 1991).…”
Section: Effects Of Wolf Predation On Ungulate Communitiessupporting
confidence: 56%
“…Also Rusakov (1979b), analyzing prey consumption by wolves in the northern part of Pskovskaya oblast (Russia) in 1968(Russia) in -1975, demon strated considerable interannual differences in prey consumption: percentage of occurrence in wolf scats ranged between 31.2-94.6% for moose and 0-10.4% for wild boar. Several authors indicated significant differences in the effect of wolf predation on ungulate communities in various seasons (especially non-snow vs snow period) (Gavrin and Donaurov 1954, Kochetkov 1988, Jędrzejewski et al 1992, Śmietana and Klimek 1993.…”
Section: Core W Olf Populations (Eastern Europe)mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, red deer was generally positively selected in central-eastern Europe (Okarma 1995;Jędrzejewski et al 2000;Andersone and Ozolins 2004;Nowak et al 2005) and in the western Alps (Gazzola et al 2005), on the contrary roe deer was selected in fewer locations of Sweden (Olsson et al 1997), Saxony (Ansorge et al 2006), Russia and Belarus (Okarma 1995). Apart from Italy, wild boar was selected as secondary prey in the Bieszczady Mountains, Poland, during winter (Smietana and Klimek 1993;Gula 2004), in two locations of central Russia and Caucasus (Okarma 1995), and as main prey only in Estonia (Valdmann et al 1998).…”
Section: Prey Selectionmentioning
confidence: 97%